Comparative study of nursing curriculum in nursing faculties of Canada, Turkey, and Iran according to SPICES model - Parvaneh Asgari; Elham Navab; Fatemeh Bahramnezhad (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Innovation in the development and review of curriculums is one of the requirements of medical education in the present era. SPICES model has been taken into consideration by nursing faculties to promote quality of nursing education and to eliminate conventional curriculums. In Iran, for competency-based nursing education, review and development of curriculums are necessary. OBJECTIVE: The objectives of the present study were to determine the implementation of SPICES model in nursing curriculums of Tehran (Iran), Western (Canada), and Hacettepe (Turkey) nursing faculties and also to present recommendations to operationalize it in the nursing curriculum of Iran. MATERIALS AND METHODS: This study using comparative method with Brady's model was conducted in 2018. In this study, curriculums of nursing faculties of Tehran, Western Canada, and Hacettepe were compared. Data were extracted through texts and documents available at electronic pages of universities. Curriculums of these nursing faculties were compared from the perspective of SPICES model strategies (student-based, problem-based, integration, community-based, elective, and systematic) at four steps of description, interpretation, juxtaposition, and comparison. RESULTS: The results showed that curriculums in Western Canada reside at the end of the innovative spectrum of SPICES model. Curriculums in Tehran and Hacettepe in most of the strategies of this model reside at the beginning of the spectrum, and in most cases, conventional methods were used. CONCLUSIONS: According to successful experiences of Western Canada in the implementation of SPICES model's strategies and also considering this fact that still conventional approaches are prevalent in Iran, it is recommended to focus on experiences and, according to social conditions and facilities of the nursing community, to implement necessary changes in the curriculums based on this model.